Discount Framing on Consumer Purchase Intention: A Literature Review - Charada, Maan (Lighthouse Publishing, 2025)
This literature review examines the relationship between discount framing and purchase intention in e-commerce contexts. Drawing on recent empirical studies, the research investigates how different discount presentation formats influence consumer purchasing behavior across various product categories and demographic segments. The analysis reveals that discount framing significantly impacts purchase intention through multiple psychological mechanisms, with effectiveness varying based on product type, consumer characteristics, and presentation format. Findings indicate that percentage and slash price discounts are more effective for specialty goods, while special price discounts better influence convenience goods. Gender differences emerge as a crucial moderating factor, with women and men responding differently to various framing approaches. Additionally, emotional factors such as anticipatory guilt play a significant mediating role, particularly for hedonic products. The review suggests that e-commerce platforms and retailers should develop targeted discount framing strategies informed by consumer psychology rather than applying uniform approaches. This research contributes to the theoretical understanding of framing effects in digital marketing while providing practical guidelines for optimizing discount presentations to enhance purchase intention ethically. The findings have implications for marketing strategy development, consumer behavior theory, and e-commerce platform design.